2021
DOI: 10.1523/eneuro.0514-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Thermal Effects of Focused Ultrasound on an Identified, Single Motoneuron

Abstract: Focused ultrasound (US) is an emerging neuromodulation technology that has gained much attention due to its ability to modulate, noninvasively, neuronal activity in a variety of animals, including humans. However, there has been considerable debate about exactly which types of neurons can be influenced and what underlying mechanisms are in play. Are US-evoked motor changes driven indirectly by activated mechanosensory inputs, or more directly via central interneurons or motoneurons?Although it has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…50 Moreover, an increase in tissue temperature would reduce but not enchance its excitability. 51,52 Therefore, the observed effects of tbTUS over the motor cortex are likely related to nonthermal effect. Although how tbTUS excites neurons via mechanical forces is not fully understood, it may induce activation of mechanosensitive voltage-gated sodium and calcium channels.…”
Section: Effects Of Tbtus On Motor Behaviormentioning
confidence: 99%
“…50 Moreover, an increase in tissue temperature would reduce but not enchance its excitability. 51,52 Therefore, the observed effects of tbTUS over the motor cortex are likely related to nonthermal effect. Although how tbTUS excites neurons via mechanical forces is not fully understood, it may induce activation of mechanosensitive voltage-gated sodium and calcium channels.…”
Section: Effects Of Tbtus On Motor Behaviormentioning
confidence: 99%
“…[20][21][22][23] The influence of mechanical vs thermal mechanisms of acoustic stimulation is debated, but it could be a differentiating factor between tFUS and TPS. [24][25][26][27] Future studies could investigate this directly. With respect to model interpretation, the consideration of intensity as a proxy for neuromodulation is rational because it indicates regions in the brain directly affected by ultrasound stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as previously mentioned, lower NSRs at 3.3 MHz may be due to difficulties in properly positioning the focal spot on the neural structure. Furthermore, it is important to consider that local temperature elevations of a few degrees may produce an inhibitory effect and thus contribute to lowering the NSR for FUS applied at 3.3 MHz 55,56 . In particular, a recent study by Collins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to consider that local temperature elevations of a few degrees may produce an inhibitory effect and thus contribute to lowering the NSR for FUS applied at 3.3 MHz. 55,56 In particular, a recent study by Collins et al on an invertebrate medicinal leech model showed that ultrasound parameters capable of generating heat (2-3 • C) induced an inhibitory response as demonstrated by a reduction of close to 43%, on average, in the firing rate of a single motoneuron. 56 Nonetheless, when studying the effects of changing the PRF and number of pulses per FUS stimulus, significant jumps in NSR were observed for very low differences in thermal elevations.…”
Section: Discussionmentioning
confidence: 99%